miR-381-3p Cooperated With Hes1 to Regulate the Proliferation and Differentiation of Retinal Progenitor Cells - Wang, Jiajing; Sun, Na; Ju, Yahan; Ni, Ni; Tang, Zhimin; Zhang, Dandan; Dai, Xiaochan; Chen, Moxin; Wang, Yiqi; Gu, Ping; Ji, Jing (Frontiers in Cell and Developmental Biology, 2022)
Retinal progenitor cells (RPCs) transplantation has become a promising therapy for retinal degeneration, which is a major kind of ocular disease causing blindness. Since RPCs have limited proliferation and differentiation abilities toward retinal neurons, it is urgent to resolve these problems. MicroRNAs have been reported to have vital effects on stem cell fate. In our study, the data showed that overexpression of miR-381-3p repressed Hes1 expression, which promoted RPCs differentiation, especially toward neuronal cells, and inhibited RPCs proliferation. Knockdown of endogenous miR-381-3p increased Hes1 expression to inhibit RPCs differentiation and promote proliferation. In addition, a luciferase assay demonstrated that miR-381-3p directly targeted the Hes1 3’ untranslated region (UTR). Taken together, our study demonstrated that miR-381-3p regulated RPCs proliferation and differentiation by targeting Hes1, which provides an experimental basis for RPCs transplantation therapy for retinal degeneration.